Dengue on the rise in Encarnación, Paraguay (2023–2024): an emerging threat to regional transmission dynamics - Dressler, Diana P; González, Mónica M; Gómez de la Fuente, Andrea; Cantero, Cesar A; Alfonzo, Tania M; Aquino, Victor H (The Journal of Infection in Developing Countries, 2025)
Introduction: Dengue remains a public health concern in Paraguay. Paraguay´s 2023–2024 epidemic was examined, emphasizing on the Itapua department in the southern region bordering Argentina. Methodology: This retrospective, cross-sectional observational study analyzed confirmed dengue cases from 17 September 2023, to 4 May 2024. Demographic and clinical data of the participants were gathered from Paraguay’s national surveillance system. Results: Among the 307,058 suspected dengue cases reported, 77,675 were confirmed through laboratory testing. The Itapua department contributed 8,310 (2.7%) and 1,910 (2.5%) of the suspected and confirmed cases; pediatric cases comprised 33% nationwide and 35% in Itapua. Intensive care needs were higher in Itapua (n = 18, 11.2%) than in other Paraguayan regions (n = 152, 2.0%). Mortality rates were also elevated in Itapua (n = 11, 0.6%) compared to the national average (n = 95, 0.13%). DENV-1 and DENV-2 were responsible for this epidemic. Encarnacion, the capital of Itapua State and a neighboring city to Posadas, Argentina, was the most severely affected (1,262 reported cases). Conclusions: The elevated rates of pediatric cases, intensive care admissions, and mortality in Itapua highlight the need for multicomponent health strategies, including enhanced vector control through community-led Aedes aegypti elimination programs and insecticide residual spraying in high-incidence zones, vaccination campaigns targeting high-risk pediatric populations with World Health Organization (WHO)-approved dengue vaccines (e.g., TAK-003), and cross-border collaboration with Argentina (e.g., Posadas-Encarnacion) to synchronize outbreak surveillance, share real-time epidemiological data, and coordinate vaccine deployment in binational hotspots.